The Impact of Internal Control System and Artificial Intelligence on the Quality of Accounting Information System and the Accuracy of Financial Reporting - Meshki Miavaghi, Mehdi; Houshmand Goorabi, Mahsa (Management Strategies and Engineering Sciences, 2025)
This study aimed to investigate the impact of the internal control system and artificial intelligence on the quality of the accounting information system and the accuracy of financial reporting and financial data reporting. The statistical population consisted of all accountants and auditors working in technology-based companies. According to the Morgan Table, a sample of 384 questionnaires was distributed and collected from the statistical population. The collected data were analyzed using SPSS version 24 and AMOS version 24 software through structural equation modeling (SEM). The results of hypothesis testing revealed that the internal control system has a positive and significant effect on the quality of the accounting information system. Artificial intelligence also has a positive and significant effect on the quality of the accounting information system. Furthermore, the internal control system has a positive and significant effect on the accuracy of financial reporting. Artificial intelligence has a positive and significant effect on the accuracy of financial reporting as well. Additionally, the quality of the accounting information system has a positive and significant effect on the accuracy of financial reporting.